2015
DOI: 10.22146/ijbiotech.8638
|View full text |Cite
|
Sign up to set email alerts
|

Histological Features of Catecholaminergic Neuron in Substantia Nigra Induced by Paraquat Dichloride (1,1-dimethyl-4,4 bipyridinium) in Wistar Rat as A Model of Parkinson Disease

Abstract: Paraquat dichloride has been used by farmers as a herbicide to kill the grass. On the other hand, paraquat dichloride is harmful if enters to the body, causing Parkinson's disease, since it is disrupting dopamine production in the substantia nigra pars compacta or dopamine pathways Nigro striatal pathway. The study was done to fi nd out the histological changes of catecholaminergic neurons and Nigro striatal pathway caused by paraquat dichloride treatment in Wistar rats as a model of Parkinson's disease.Twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…Similarly, Shimizu et al 15 found that constant exposure to low levels of PQ affected dopaminergic neurons in the nigrostriatal system of rats. More recently, Pangestiningsigh et al 16 report a decrease in the density of catecholaminergic neurons in the SNpc using histochemical preparations from rats subjected to intraperitoneal injection of PQ (15 mg/kg) over a 6-week period. 16 Laboratory investigation into animal models of PD clearly implicates PQ as a dopamine neurotoxin via chronic low-level exposure.…”
Section: Part I: Laboratory Context Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Shimizu et al 15 found that constant exposure to low levels of PQ affected dopaminergic neurons in the nigrostriatal system of rats. More recently, Pangestiningsigh et al 16 report a decrease in the density of catecholaminergic neurons in the SNpc using histochemical preparations from rats subjected to intraperitoneal injection of PQ (15 mg/kg) over a 6-week period. 16 Laboratory investigation into animal models of PD clearly implicates PQ as a dopamine neurotoxin via chronic low-level exposure.…”
Section: Part I: Laboratory Context Animal Modelsmentioning
confidence: 99%
“…More recently, Pangestiningsigh et al 16 report a decrease in the density of catecholaminergic neurons in the SNpc using histochemical preparations from rats subjected to intraperitoneal injection of PQ (15 mg/kg) over a 6-week period. 16 Laboratory investigation into animal models of PD clearly implicates PQ as a dopamine neurotoxin via chronic low-level exposure. For example, intraperitoneal injection of 10 mg/kg PQ in mice injected at varied intervals for up to 3 weeks cause decreased or altered locomotor activity in conjunction with a number of physiological symptoms occurring in a dose-dependent manner, including significant decline in dopamine levels within the striatum, loss of dopaminergic neurons, degeneration of the nigrostriatal dopamine system, aggregate formation in the SNpc containing α-synuclein, and formation of LBs.…”
Section: Part I: Laboratory Context Animal Modelsmentioning
confidence: 99%
“…Immunohistochemical staining using the primary antibody anti-TH to detect DA neurons has been reported by many researchers [ 17 - 19 ]. The TH-IR found in this study were similar to those reported by Nair-Roberts et al .…”
Section: Discussionmentioning
confidence: 99%
“…Mengecilnya ukuran neuron katekolaminergik pada kelompok perlakuan kemungkinan karena proses degenerasi. Penelitian sebelumnya menunjukkan bahwa pemberian PQ juga menyebabkan penurunan densitas neuron katekolaminergik pada substansia nigra pars kompakta tikus [22] serta terjadi penurunan jumlah neuron katekolaminergik [23]. Ada 3 macam neuron katekolaminergik yaitu neuron dopaminergik, noradrenergik dan adrenergik.…”
Section: Neuron Penyusun Sse Yang Diwarnai Imunohistokimia Menggunakan Antibodi Tirosin Hidroksilase (Th)unclassified